2018
DOI: 10.5194/isprs-annals-iv-1-163-2018
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Using Fully Convolutional Network for Treetop Detection on Remote Sensing Data

Abstract: <p><strong>Abstract.</strong> Individual tree detection and counting are critical for the forest inventory management. In almost all of these methods that based on remote sensing data, the treetop detection is the most important and essential part. However, due to the diversities of the tree attributes, such as crown size and branch distribution, it is hard to find a universal treetop detector and most of the current detectors need to be carefully designed based on the heuristic or prior know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…First, the CHM of each study area is pre-processed by applying different vegetation masks (VMs) to remove irrelevant pixels. Then, the positions of the treetops are automatically detected with a method based on the work of Xiao et al (2018) that uses the morphological Top-Hat by Reconstruction (THR) operation. 35 Last, those treetop positions are utilised as seeds for delineating the tree crowns with the RG segmentation algorithm following the work of Dalponte and Coomes (2016).…”
Section: Methodsmentioning
confidence: 99%
“…First, the CHM of each study area is pre-processed by applying different vegetation masks (VMs) to remove irrelevant pixels. Then, the positions of the treetops are automatically detected with a method based on the work of Xiao et al (2018) that uses the morphological Top-Hat by Reconstruction (THR) operation. 35 Last, those treetop positions are utilised as seeds for delineating the tree crowns with the RG segmentation algorithm following the work of Dalponte and Coomes (2016).…”
Section: Methodsmentioning
confidence: 99%
“…, 2014), human action recognition (Ji et al. , 2013), remote sensing (Xiao et al. , 2018), structural health monitoring (Cha et al.…”
Section: Bayesian Optimized Convolutional Neural Network (Bocnn)mentioning
confidence: 99%
“…As an advanced version of ANN, Convolutional Neural Networks (CNN) have been widely used in face recognition (Lawrence et al, 1997;, speech recognition (Abdel-Hamid et al, 2014), human action recognition (Ji et al, 2013), remote sensing (Xiao et al, 2018), structural health monitoring (Cha et al, 2017;Abdeljaber et al, 2017;Gopalakrishnan et al, 2017), and geotechnical engineering (Wang and Goh, 2021). Previous studies have demonstrated that CNN can not only effectively capture the topology of images but also properly identify the complicated relationship between soil parameters and the performance of geotechnical structures (Wang and Goh, 2021;He et al, 2021;Wang, 2022).…”
Section: Bayesian Optimized Convolutional Neural Network (Bocnn)mentioning
confidence: 99%
“…In research similar to ours, Xiao et al [41] used a Fully Convolutional Network (FCN) [42] to detect treetops in satellite imagery. They fused the NDVI values, the DSM, and the red band into a 3-channel input.…”
Section: Deep Learning For Plant Detectionmentioning
confidence: 99%